ANALISIS PENERAPAN DISIPLIN DAN PENEGAKAN HUKUM PROTOKOL KESEHATAN DI KOTA CIREBON - Mitha Masitoh; Nur Rahman; Sarip Sarip; Rohadi Rohadi (Jurnal De Jure Muhammadiyah Cirebon, 2020)
Coronavirus Disease (Covid-19). In 2020, a new type of coronavirus (SARS-CoV-2) was spread, called a disease called Coronavirus disease 2019 (COVID-19). This virus was discovered in Wuhan, China for the first time and has infected 90,308 people as of March 2, 2020. The number of deaths reached 3,087 people or 6%, the number of patients recovering 45,726 people. This type of single positive RNA strain infects the human respiratory tract and is sensitive to heat and can effectively be activated by chlorinecontaining disinfectants. The source of the host is thought to come from animals, especially bats, and other vectors such as bamboo rats, camels and ferrets. Common symptoms include fever, cough and difficulty breathing. Clinical syndrome is divided into uncomplicated, mild pneumonia and severe pneumonia. Specimen examination is taken from the throat swab (nasopharynx and oropharynx) and lower airway (sputum, bronchial rinse, endotracheal aspirate). Isolation was carried out on patients proven to be infected with Covid-19 to prevent wider spread. Keywords: Coronavirus; Covid-19; Pneumonia; Wuhan.